Impact of technical water retention on European beech (Fagus sylvatica L.) resilience and growth dynamics - Zdeněk Vacek; Ivana Tomášková; Zdeněk Fuchs; Václav Šimůnek; Stanislav Vacek; Jan Cukor; Lukáš Bílek; Josef Gallo; Karel Zlatuška; Martin Duchan (Journal of Forest Science)
Global climate change (GCC) is putting increasing pressure on forest ecosystems, leading to more frequent disturbances such as pest outbreaks and other climate-related stressors, all of which threaten forest stability. This study examines how different technical water retention measures (infiltration pits) can enhance the resilience of European beech (Fagus sylvatica L.) to these climatic challenges, focusing on their impact on radial growth, sap flow, and acclimatisation to moisture conditions at two sites in Czechia (430-440 m a.s.l.). Three treatments were compared: a water infiltration pit under a culvert mouth, an infiltration pit without a culvert and a control plot without a technical solution. Results showed that maximum daily transpiration rates of beech ranged between 90-120 L per day. Air temperature had a stronger influence on beech radial growth than precipitation, particularly at the waterlogged sites. The lowest radial growth occurred in the treatment involving a water infiltration pit under a culvert mouth, while treatments with an infiltration pit without a culvert demonstrated notable seasonal stem shrinkage and swelling (tree water deficit - TWD), especially in early spring. On the other hand, no differences were found between the three treatments including the control variant in the maximum growth or the context of minimum TWD. In conclusion, these technical measures had limited or short-term effects on the growth and physiological processes of European beech. Despite the high costs of implementation, sap flow and dendrochronological measurements do not support the construction of infiltration pits as a means of improving water retention in forest ecosystems.